Priesthood and temple in John's apocalypse: constructing the sanctuary - Tse, Timothy B. (The Library of New Testament Studies, 2024)
Intro -- Half Title -- Title Page -- Copyright Page -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Chapter 1: Introducing the Problem -- 1.1. Literature Review -- 1.1.1. Interpreting Space -- 1.1.2. Interpreting Sanctuary Imagery -- 1.1.3. Interpreting Priesthood -- 1.1.4. Interpreting Time -- 1.1.5. Summary -- 1.2. Methodology -- 1.2.1. Communication and Relevance Theory -- 1.2.2. Reconstructing Revelation's Cognitive Environment(s) -- 1.2.3. Summary -- 1.3. Plan -- Chapter 2: The Cosmos in John's Apocalypse -- 2.1. The Three-Tiered Cosmos in John's Visionary World -- 2.2. The Continuous Cosmos -- 2.3. The Entangled Cosmos -- 2.4. Conclusion -- Chapter 3: The Earth Is a Sanctuary -- 3.1. How to Build a Sanctuary Outside the New Testament -- 3.1.1. The Earthly Sanctuary in Firstspace -- 3.1.2. The Earthly Sanctuary in Secondspace -- 3.1.3. Conclusion -- 3.2. Building a Sanctuary in the New Testament Outside of Revelation -- 3.2.1. The Gospels and the ναός -- 3.2.2. Paul and the Church as ναός -- 3.2.3. Hebrews and the Heavenly Tabernacle -- 3.2.4. Continuity and Discontinuity in the New Testament ναός -- 3.2.5. Summary -- 3.3. The Missing Earthly Sanctuary in Revelation -- 3.3.1. Heaven Has a ναός Building -- 3.3.2. The Missing ναός in the New Jerusalem -- 3.3.3. God and the Lamb Do Not Completely Replace the Sanctuary -- 3.3.4. The New Jerusalem Does Not Represent the church as Sanctuary -- 3.3.5. Summary -- 3.4. The Earth as Sanctuary in Revelation -- 3.4.1. The Holy of Holies -- 3.4.2. Outside the Walls of the New Jerusalem -- 3.4.3. The Holy Place -- 3.4.4. The Sanctuary Courtyard -- 3.4.5. A Note on the Old and New Creation -- 3.5. Conclusion -- Chapter 4: The Saints Are Its Priests -- 4.1. The Priestly Characterization of the Saints -- 4.2. Levitical Priesthood Is the Baseline in the Second Temple Era.